Converting Agricultural Land To Mining From The Perspective Of Islamic Economic Law - Alfiandi Zikra (Journal Economy and Currency Study (JECS), 2022)
The conversion of agricultural land to non-agricultural functions has become a phenomenon in almost all regions. With the aim of increasing the economy instantly and quickly One thing that may not be taken into consideration in carrying out land conversion is the impact arising from the conversion of land functions, both in terms of the declining agricultural output sector or environmental damage due to the transfer of functions. One of the conversions of agricultural land to mining occurred in Pangkalan Jambu District, Merangin Regency, Jambi Province. The data analysis method of this research is descriptive. The findings of this study are: First, in the process of converting agricultural land into mining in Pangkalan Jambu District, Merangin Regency, Jambi Province, the majority of people still use manual tools, Second, the conversion of agricultural land into mining in Pangkalan Jambu District, Merangin Regency, Jambi Province has a significant impact on community economic improvement. However, the impact of environmental damage is much greater. Third, in the study of Islamic economic law, the conversion of agricultural land to mining in Pangkalan Jambu District, Merangin Regency, Jambi Province violates the concept of maslahah.